Pengaruh Kesadaran Merek (Brand Awareness) terhadap Keputusan Pembelian Handphone Samsung - Arman Paramansyah; Dipo Mirza Ghulam; Ernawati Ernawati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2020)
Until now, Samsung is one of the largest mobile phone brands in the world by issuing smartphones that have won the competition in the smartphone market. This research was conducted with the aim, to determine how the relationship between brand awareness and purchasing decisions, and to find out how the influence of brand awareness on purchasing decisions for Samsung mobile phones. The independent variable in this study is brand awareness, the dependent variable is the purchase decision. The population in this study were students of IAI-N Laa Roiba, Bogor, Faculty of Sharia. Sampling was carried out using the Slovin formula, in order to obtain a total sample of 34 students. Data collection using questionnaires and observations. Statistical data analysis used simple linear regression, with hypothesis testing through t-test using the SPSS version 25 program. The results of this study indicate that there is a positive and significant effect of brand awareness on the decision to buy cellphones because the terms of t count with a significance value <0.05, namely 4.027> 2.032 and the Sig. 0,000 <0.05, has been fulfilled.